The bacteriome at the onset of type 1 diabetes: A study from four geographically distant African and Asian countries - Cinek, Ondrej; Kramna, Lenka; Mazankova, Karla; Odeh, Rasha; Alassaf, Abeer; Ibekwe, MaryAnn Ugochi; Ahmadov, Gunduz; Elmahi, Bashir Mukhtar Elwasila; Mekki, Hanan; Lebl, Jan; Abdullah, Mohammed Ahmed (Diabetes research and clinical practice, 2018)
OBJECTIVES: Gut bacteriome profiling studies in type 1 diabetes (T1D) to date are mostly limited to populations of Europe, with two studies from China and one study each from Mexico and the USA. We therefore sought to characterize the stool bacteriome in children after onset of T1D along with age- and place-matched control subjects from four geographically distant African and Asian countries. METHODS: Samples were collected from 73 children and adolescents shortly after T1D onset (Azerbaijan 19, Jordan 20, Nigeria 14, Sudan 20) and 104 matched control subjects of similar age and locale. Genotyping of major T1D susceptibility genes was performed using saliva or blood samples. The bacteriome was profiled by next-generation sequencing of 16S rDNA. Negative binomial regression was used to model associations, with adjustment for the matched structure of the study. RESULTS: A significant positive association with T1D was noted for the genus Escherichia (class Gammaproteobacteria, phylum Proteobacteria), whereas Eubacterium and Roseburia, two genera of class Clostridia, phylum Firmicutes, were inversely associated with T1D. We also confirmed a previously observed inverse association with Clostridium clusters IV or XIVa. No associations were noted for richness, evenness, or enterotypes. CONCLUSIONS: Based on our results, some type of distortion of the gut bacteriome appears to be a global feature of T1D, and our findings for four distant populations add new candidates to the existing list of bacteria. It remains to be established whether the observed associations are markers or causative factors.
Keywords: dospělí; Female; Asia; feces; Feces; dítě; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; Gastrointestinal Microbiome; High-Throughput Nucleotide Sequencing; Afrika; Adolescent; RNA, Ribosomal, 16S; bakteriální RNA; lidé; Type 1 diabetes; Diabetes Mellitus, Type 1; Male; Bacteria; střevní mikroflóra; Africa; mladiství; vysoce účinné nukleotidové sekvenování; Child, Preschool; RNA, Bacterial; Young Adult; Bacteriome imbalance; 16S rDNA sequencing; Asie; Child; mužské pohlaví; RNA ribozomální 16S; diabetes mellitus 1. typu; Humans